Antisense Oligonucleotide (AON)-based Therapy for Leber Congenital Amaurosis Caused by a Frequent Mutation in CEP290 - Rob WJ Collin; Anneke I den Hollander; Saskia D van der Velde-Visser; Jeannette Bennicelli; Jean Bennett; Frans PM Cremers (Elsevier, 2012)
Leber congenital amaurosis (LCA) is the most severe form of inherited retinal degeneration, with an onset in the first year of life. The most frequent mutation that causes LCA, present in at least 10% of individuals with LCA from North-American and Northern-European descent, is an intronic mutation in CEP290 that results in the inclusion of an aberrant exon in the CEP290 mRNA. Here, we describe a genetic therapy approach that is based on antisense oligonucleotides (AONs), small RNA molecules that are able to redirect normal splicing of aberrantly processed pre-mRNA. Immortalized lymphoblastoid cells of individuals with LCA homozygously carrying the intronic CEP290 mutation were transfected with several AONs that target the aberrant exon that is incorporated in the mutant CEP290 mRNA. Subsequent RNA isolation and reverse transcription-PCR analysis revealed that a number of AONs were capable of almost fully redirecting normal CEP290 splicing, in a dose-dependent manner. Other AONs however, displayed no effect on CEP290 splicing at all, indicating that the rescue of aberrant CEP290 splicing shows a high degree of sequence specificity. Together, our data show that AON-based therapy is a promising therapeutic approach for CEP290-associated LCA that warrants future research in animal models to develop a cure for this blinding disease.